2006
DOI: 10.1111/j.1460-9568.2006.04675.x
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory sensory neurons expressing class I odorant receptors converge their axons on an antero‐dorsal domain of the olfactory bulb in the mouse

Abstract: Vertebrate odorant receptor (OR) genes are divided phylogenetically into two distinct classes: the fish-like class I and the terrestrial-specific class II. In the present study, we systematically analysed mouse class I OR genes (42 subfamilies) to elucidate the expression profiles in the olfactory epithelium (OE) and the projection sites of their olfactory sensory neurons (OSNs) in the olfactory bulb (OB). In situ hybridization (ISH) revealed that most class I OR genes (36 subfamilies) were expressed in the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 45 publications
(69 reference statements)
2
73
0
Order By: Relevance
“…Class I and class II ORs are phylogenetically distinct, and their glomeruli are segregated into the DI and DII regions of the dorsal OB, respectively ( Fig. 1 A) (Zhang et al, 2004;Miyamichi et al, 2005;Tsuboi et al, 2006;Kobayakawa et al, 2007;Bozza et al, 2009). Activation of glomeruli in these two regions has been linked to innate avoidance responses to aversive odors, such as those emanating from spoiled food and predator urine (Kobayakawa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Class I and class II ORs are phylogenetically distinct, and their glomeruli are segregated into the DI and DII regions of the dorsal OB, respectively ( Fig. 1 A) (Zhang et al, 2004;Miyamichi et al, 2005;Tsuboi et al, 2006;Kobayakawa et al, 2007;Bozza et al, 2009). Activation of glomeruli in these two regions has been linked to innate avoidance responses to aversive odors, such as those emanating from spoiled food and predator urine (Kobayakawa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The staining of axons indicates a prominent transcytosis in the olfactory sensory neurons (Hocini et al, 2001;Miller et al, 1994). It is tempting to associate such a transcytosis with the essential role of odorant receptors in targeting axonal projection to precise sites in the olfactory bulb Tsuboi et al, 2006;Wang et al, 1998). The participation of odorant receptors in targeting requires transport of these receptors to the axon terminals, and ligand-specific endocytosis may play a part in such processes.…”
Section: Endocytosismentioning
confidence: 99%
“…Although Class I ORs are mostly expressed within the D zone (Zhang et al, 2004;Tsuboi et al, 2006), class II OR genes are expressed in both D and V zones. Within the D zone, class I and class II expressing cells are intermingled and there is no restricted distribution for both classes (Tsuboi et al 2006). In the V zone, however, each class II OR gene possesses its unique expression area, distributed in a continuous and overlapping manner along the dorsomedial -ventrolateral axis in the OE (Miyamichi et al 2005).…”
Section: Spatial Organization Of the Rodent Olfactory Epithelium And mentioning
confidence: 99%
“…1B). Systematic in situ hybridization and genetic labeling indicated that OSNs expressing class I ORs project their axons to the most anterodorsal areas (DI) within the D domain (Tsuboi et al 2006;Kobayakawa et al 2007;Bozza et al 2009). The OR-specific expression area along the dorsomedial-ventrolateral axis of the V zone OE is well correlated with D-V positioning of glomeruli in the OB (Miyamichi et al 2005).…”
Section: Mechanisms Of Olfactory Map Formation In Mammals Topographicmentioning
confidence: 99%
See 1 more Smart Citation